2011
DOI: 10.2215/cjn.09011010
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Specific Mortality in Chronic Kidney Disease

Abstract: SummaryBackground and objectives Chronic kidney disease (CKD) is known to be associated with increased allcause and cardiovascular mortality, but no large studies examined the cancer-specific mortality in non-dialysis-dependent CKD patients. Such outcome data are needed for proper allocation of resources and would help to develop better preventive services. Between 1998 and 1999, 123,717 adults were recruited from four health screening centers in Taiwan. The estimated glomerular filtration rate was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
105
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 34 publications
15
105
1
Order By: Relevance
“…7,19 However, details about malignancy-related deaths are sparse, and a recent report from Taiwan indicated that patients with CKD had a higher mortality risk from liver, kidney, and urinary tract cancer. 20 Our results also highlight the leading causes of malignancy-related deaths (Supplemental Table 3) among the CKD population followed in our healthcare system. Overall, these higher numbers of cancer-related deaths could be attributed to the fact that a large proportion of patients receiving care for cancer at our healthcare system had underlying CKD or develop CKD during the treatment course.…”
Section: Discussionsupporting
confidence: 60%
“…7,19 However, details about malignancy-related deaths are sparse, and a recent report from Taiwan indicated that patients with CKD had a higher mortality risk from liver, kidney, and urinary tract cancer. 20 Our results also highlight the leading causes of malignancy-related deaths (Supplemental Table 3) among the CKD population followed in our healthcare system. Overall, these higher numbers of cancer-related deaths could be attributed to the fact that a large proportion of patients receiving care for cancer at our healthcare system had underlying CKD or develop CKD during the treatment course.…”
Section: Discussionsupporting
confidence: 60%
“…13 A separate study has also observed increased renal and urothelial cancer-specific mortality among patients with CKD. 16 Among a much larger, diverse population-based sample, we did not find GFR to be an independent predictor of overall cancer risk or specific cancers, such as prostate, breast, lung, or colorectal, after rigorously adjusting for potential confounders and excluding any incident cancers diagnosed within the first 2 years of followup and all GFR measurements within 3 months before a cancer diagnosis. Our findings reveal that the association of CKD and cancer risk is site-specific for renal and urothelial cancers and does not seem to be associated with an individual's overall cancer risk.…”
Section: Discussionmentioning
confidence: 58%
“…We did not collect data specific for the type of cancers in our study and until further analysis is done we cannot establish a causal link between CKD and cancer risk. In any case, CKD was associated with increased cancer-specific mortality than general population 20 and interventions to reduce the risk of cancer and improve the outlook for those who develop cancer are needed.…”
Section: Discussionmentioning
confidence: 99%